Implementation of Merdeka Belajar-Kampus Merdeka in The Perspective of Communication Based Learning - Yahya, Ahmad Harun; Nur, Dalinur M; Walian, Anang; Pohan, Hasril Atieq; Jawasi, Jawasi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This research aims to discover the policies, efforts made by the study program, and implementation of Merdeka Belajar-Kampus Merdeka from the perspective of communication-based learning. The type of data for this research is qualitative. Data collection techniques use interviews, observation, and documentation data analysis techniques using data reduction, data presentation, and verification/concluding. Triangulating sources carried out data validity by comparing interview data, observation, and documentation. The results of this research found that first, UIN Raden Fatah Palembang's policy in preparing MBKM regulations was to create MBKM guidelines, provide facilities to fulfill study periods and loads, collaborate with other universities and partners in the business and industrial world, carry out monitoring and evaluation of MBKM implementation; and reviewing the MBKM-based study program curriculum. Second, the preparatory efforts carried out by the study program are holding benchmarking, seminars, and workshops; Best-Q training; offering courses that can be taken into MBKM both outside the study program and outside the campus; verifying students who will take part in the MBKM program according to the specified requirements; placing both internal and external students in study groups according to applications; carry out course equivalence; carry out the learning process if several subjects have not been fulfilled from learning activities outside the study program and the university; and report the implementation of MBKM to the faculty every semester. Third, the Merdeka Belajar – Merdeka Campus regulations from a Communication-Based Learning perspective is that MBKM needs Communication Based Learning, study programs, and students must be more active in communicating with study programs, other campuses, agencies, and the world of business and industry (DUDI); optimizing the use of electronic learning media (e-learning); optimizing the use of new media learning media; and optimizing communication with alumni through tracer studies, carer development centers (CDC).